Design and Implementation of a Long Range Wireless Data Acquisition System for Photovoltaic Installation based on LoRa Technology - Boulemzaoud, L.; Latreche, S.; Khemliche, M. (Engineering, Technology & Applied Science Research, 2022)
In this paper, a low power consumption long range wireless data acquisition system for PV installations, consisting of a set of sensors connected wirelessly with one or several monitoring/control systems was designed and implemented. The wireless communication between devices is based on LoRa technology. LoRa is a spread spectrum modulation technique derived from Chirp Spread Spectrum (CSS) technology. It offers a long-range low power wireless platform, suitable for professional wireless sensor network applications. The integration of this technology in PV installations provides an extensive, low cost, power-efficient, and easy to maintain, system. Design, high-layer communication protocol, and hardware implementation of sensors are discussed. The sensor set consists of a voltage/current sensor, a sun irradiance sensor, a panel position sensor based on an accelerometer/magnetometer for sun tracking installations, a temperature and humidity sensor, and a mobile monitoring system.